Differential Monocyte Actuation in a Three‐Organ Functional Innate Immune System‐on‐a‐Chip. Issue 13 (2nd June 2020) - Sasserath, Trevor; Rumsey, John W.; McAleer, Christopher W.; Bridges, Lee Richard; Long, Christopher J.; Elbrecht, Daniel; Schuler, Franz; Roth, Adrian; Bertinetti‐LaPatki, Christina; Shuler, Michael L.; Hickman, James J.
Abstract: A functional, human, multiorgan, pumpless, immune system‐on‐a‐chip featuring recirculating THP‐1 immune cells with cardiomyocytes, skeletal muscle, and liver in separate compartments in a serum‐free medium is developed. This in vitro platform can emulate both a targeted immune response to tissue‐specific damage, and holistic proinflammatory immune response to proinflammatory compound exposure. The targeted response features fluorescently labeled THP‐1 monocytes selectively infiltrating into an amiodarone‐damaged cardiac module and changes in contractile force measurements without immune‐activated damage to the other organ modules. In contrast to the targeted immune response, general proinflammatory treatment of immune human‐on‐a‐chip systems with lipopolysaccharide (LPS) and interferon‐ γ (IFN‐ γ ) causes nonselective damage to cells in all three‐organ compartments. Biomarker analysis indicates upregulation of the proinflammation cytokines TNF‐ α, IL‐6, IL‐10, MIP‐1, MCP‐1, and RANTES in response to LPS + IFN‐ γ treatment indicative of the M1 macrophage phenotype, whereas amiodarone treatment only leads to an increase in the restorative cytokine IL‐6 which is a marker for the M2 phenotype. This system can be used as an alternative to humanized animal models to determine direct immunological effects of biological therapeutics including monoclonal antibodies, vaccines, and gene therapies, and the indirect effects caused by cytokine release from target tissues in response to a drug's pharmacokinetics (PK)/pharmacodynamics (PD) profile. Abstract : A functional, human, multiorgan, pumpless, immune system‐on‐a‐chip containing recirculating THP‐1 immune cells with cardiomyocytes, skeletal muscle, and liver compartments with a serum‐free medium is developed. This system emulates both a targeted immune response to tissue‐specific damage and a holistic immune response to proinflammatory compound exposure. These immune responses are reflected in changes to parenchymal cell functionality and cytokine release.